Electrochemical analysis of antioxidant status of biological media in different sampling and storage conditions - Goroncharovskaya Irina V.; Evseev Anatoly K.; Shabanov Aslan K.; Petrikov Sergey S. (Journal of the Serbian Chemical Society, 2024)
The use of an electrochemical approach for assessment of the oxidative stress severity is a promising direction for point-of-care testing development, which is especially important for critically ill patients. The aim of this study was to determine the influence of different types of blood collection tubes (with clot activator and separating gel, lithium heparin, sodium citrate and K2EDTA) and storage conditions (at 25, 4 and –23 °C up to 5 days) on the electrochemical analysis of the antioxidant status of blood plasma, assessed by measuring the open circuit potential of platinum electrode (OCP) and antioxidant capacity via cyclic voltammetry method (q). It was obtained that blood collection tubes with lithium heparin and clot activator are the most suitable for the electrochemical analysis of antioxidant status of blood plasma, since they do not affect the results of measurements. Furthermore, data obtained during storage blood plasma samples in different temperature conditions indicate that it is preferable to perform electrochemical analysis in fresh samples.